Structured Questioning for Equitable Classroom Participation and Higher-Order Moral Reasoning in Aqidah Akhlak Education - Roslaini; Yuliana Afifah; Ismail Fahri; M Thontawi; Husarida (WISE Pendidikan Indonesia, 2026)
Aqidah Akhlak learning in madrasahs often emphasizes memorization and teacher-centered instruction, limiting students’ opportunities to engage in analytical, evaluative, and creative moral reasoning. This study aimed to enhance students’ higher-order thinking skills through structured questioning techniques in Aqidah Akhlak learning. Using Classroom Action Research, the study was conducted in two cycles involving 26 eleventh-grade science students at an Islamic senior high school in Jambi, Indonesia. Each cycle consisted of planning, action, observation, and reflection. Data were collected through HOTS-based written tests, classroom observation sheets, teacher interviews, field notes, and documentation. The intervention used open-ended, probing, evaluative, and reflective questions supported by scaffolding, wait time, peer discussion, and constructive feedback. The findings showed a substantial improvement in students’ classroom participation and HOTS achievement. Active participation increased from 38.5% in Cycle I to 73.1% in Cycle II, while the mean HOTS score rose from 68.4 to 82.7. The proportion of students achieving the minimum mastery criterion also increased from 57.7% to 84.6%. Improvements were observed across analysis, evaluation, and creation dimensions. These findings indicate that structured questioning techniques can transform Aqidah Akhlak learning into a more dialogic, reflective, and inclusive process that supports students’ moral reasoning and higher-order thinking.